A taxonomic revision of the African leaf chafer genus Asthenopholis Brenske, 1898 (Coleoptera: Scarabaeidae: Melolonthinae): a SEM study - Harrison, James Du G. (Zootaxa, 2009)
The African chafer genus Asthenopholis Brenske, 1898 is revised. Seven species are included in the genus: A. adspersa (Boheman, 1857), A. crypsis sp. nov., A. crassa Arrow, 1902, A. minor Brenske, 1898, A. subfasciata (Blanchard, 1851), A. ugandensis Moser, 1913, and A. rex sp. nov. Asthenopholis transvaalensis Brenske, 1898 is here designated as the type species for the genus. The synonymy of A. transvaalensis Brenske, 1898 with A. adspersa (Boheman, 1857) is maintained. Lectotypes are designated for Asthenopholis adspersa (Boheman, 1857), A. dasypus (Burmeister, 1855), A. minor Brenske, 1898, A. subfasciata (Blanchard, 1851), A. transvaalensis Brenske, 1898, and A. ugandensis Moser, 1913. In the absence of a formal description, Asthenopholis bechuana Péringuey, 1904 is regarded as a nomen nudum. Colour habitus pictures and three views of the male genitalia are provided for all valid species. A key to differentiate the species and three maps to illustrate their known distributions are included. The phenology (as seven bar charts) and pest status are presented for all species. Fourteen plates comprising 138 scanning electron micrographs are included to illustrate obscure, yet species-specific characters (including some generic-specific characters).